PENGARUH UANG SAKU BULANAN DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF MAHASISWA KOST (Studi Kasus Pada Mahasiswa Kost Daerah Sukarame) - Ellen Praditha; Karina Ismalia; Vicky F. Sanjaya (Jurnal Ekonomi Regional Unimal, 2022)
This study aims to determine: 1) The effect of monthly allowances on the consumptive behavior of boarding students in the Sukarame area. 2) The Influence of Lifestyle on Consumptive Behavior of Boarding School Students in the Sukarame area.  The model used in data analysis is multiple linear regression. The analytical tool used in this study is SmartPLS 3.0. The data used, namely primary and secondary data by taking samples, namely purposive sampling. The research results show that 1) Monthly Allowance has a positive and significant effect as indicated by the probability valuefor the Monthly Pocket Money variable which is 0.213 <0.05. 2) Lifestyle has a positive and significant effect as indicated by the probability value for the pocket money variable is 0.590 <0.05